The Price of Leadership - Charlie "Tremendous" Jones (Mechanicsburg Tremendous Life Books, 2010)
The late Charlie Tremendous Jones was a publisher, motivator, and humorist who gained a reputation as one of the most dynamic and funniest speakers in the country.
Keywords: Leadership